ANALISIS PENDAPATAN DAN NILAI TAMBAH USAHA PRODUK OLAHAN NIRA AREN (GULA AREN) DI DESA MONGIILO KECAMATAN BOULANGO ULU KABUPATEN BONE BOLANGO - Ibrahim, Nurain; Indriani, Ria; Sirajuddin, Zulham (Universitas Islam Balitar, 2024)
The objectives of this study are twofold: firstly, to assess the viability of processing palm sugar products, and secondly, to determine the additional value that palm sugar brings to Mongiilo Village in the Bone Bolango Regency. This investigation spanned from September to December 2022, involving 67 farmers as respondents. The research utilized both primary and secondary data. Employing a saturated sampling method (census), all respondents were interviewed, ensuring a comprehensive representation of the population. The analytical approach adopted for assessing added value was the hayami method, while the Return Cost Ratio (R/C Ratio) was employed for overall analysis. The findings revealed an R/C ratio of 3.72, surpassing the threshold of 1. This implies that cultivating palm sugar in Mongiilo Village, Bulango Ulu District, Bone Bolango Regency, is economically justified. The study determined an added value of Rp. 761.11/kg, with palm sugar craftsmen in Mongiilo Village generating a profit of Rp. 587.83, equivalent to 19.59% of the total production.